Exact Loop Wave Solutions and Cusp Wave Solutions of the Fujimoto-Watanabe Equation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the theory of dynamical systems is employed toinvestigate loop waves and cusp waves of the Fujimoto-Watanabe equation.These waves contain solitary loop waves, periodic loop waves, peakons andperiodic cusp waves. Under fixed parameter conditions, their exact explicitparametric expressions are given.